Penentuan Lokasi Distributor dengan Menggunakan Analytical Hierarchy Process dan Skala Liberatore - Dyah Kusmindarti (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
Based on the natural problems of company, researcher try to give alternative trouble-shooting of decision making by using Method of Analytical Hierarchy Process (AHP) and supported with Method 5 Scale of Liberatore. After doing assessment to criterion sub and criterion with method of AHP later in continuing with assessment 5 Scale of Liberatore from each criterion sub with giving one of scale size measure which consist of outstanding (O), good (G), average (A), fair (F) and poor (P) in each criterion sub to know biggest global weight among some alternative location to be selected. And chosen distributor location I region of Jakarta because having biggest global weight that is 0.401 with criterion weight of marketing factor equal to 0.481, Expense of equal to 0.114 and Continuity of Product equal to 405, while Region of Semarang (alternative to II) and Magelang (Alternative to III) weight of global successively equal to 0.354 and 0.245.